Effects of soil water deficit and nitrogen nutrition on water relations and photosynthesis of pot-grown Coffea canephora Pierre - DaMatta, Fábio M.; Loos, Rodolfo A.; Silva, Emerson A.; Loureiro, Marcelo E.; Ducatti, Carlos (Springer Nature, 2002)
Coffea canephora plants (clone INCAPER-99) were submitted to low N (LN) or high N (HN) applications and two watering regimes (daily irrigation and irrigation every 5 days for a month). Although water potential was not altered significantly by N, HN plants showed higher relative water content than did LN plants under water deficit. Only HN plants exhibited some ability for osmotic adjustment. Plants from both N treatments increased their cell wall rigidity under drought, with a more pronounced augmentation in HN plants. In well-watered plants, carbon assimilation rate increased with increasing N while stomatal conductance did not respond to N supply. Under drought conditions, carbon assimilation decreased by 68-80% compared to well-watered plants, whereas stomatal conductance and transpiration rate declined by 35% irrespective of the N applications. Stable carbon isotope analysis, combined with leaf gas exchange measurements, indicated that regardless of the watering treatments, N increased the long-term water use efficiency through changes in carbon assimilation with little or no effect on stomatal behaviour.
Keywords: Carbon isotope composition; Coffee; Drought; Water deficit; Water use efficiency; Irrigation; Nitrogen; Nutrition; Plants (botany); Soils; Stomatal conductance; Watering; Water; Nutrients; Plants; Soil; Coffea canephora